Development of android apps for matrix operations - Tea, Mi Wen (Nanyang Technological University, 2024)
The prevalence of machine learning in contemporary technology often remains unnoticed, despite its pivotal role in advancements such as Optical Character Recognition (OCR). This project aims to develop an Android application that brings matrix operations to the forefront of educational tools. The application provides a tangible platform for both students and educators to interact with these essential computations.